The analgesic effects of quadratus lumborum block versus caudal block for pediatric patients undergoing abdominal surgery: a systematic review and meta-analysis - Yu Zhu; Jin Wu; Shenglong Qu; Peng Jiang; Chetan Bohara; Chetan Bohara; Yi Li (Frontiers in Pediatrics)
BackgroundSince children cannot express pain, postoperative pain treatment for them is relatively lacking. In this meta-analysis, we compared the postoperative analgesic effects of quadratus lumborum block (QLB) and caudal block (CB) in surgeries involving the lower abdomen, inguinal region, and urogenital system in children.ObjectiveThis review examined the postoperative analgesic effects of QLB and CB in pediatric patients (0–18 years of age) undergoing abdominal surgery. The primary endpoint was the rate of postoperative rescue analgesia, defined as the proportion of patients who returned to acetaminophen, ibuprofen, and other analgesics when the pain score was greater than the protocol preset value within 24 h after surgery. Secondary outcomes included resting pain scores (0–10) at 30 min, 4 h, 12 h, and 24 h after surgery. Other secondary outcome measures were the time of first rescue analgesia, the incidence of PONV, and the incidence of postoperative complications, such as post-block infection, anaphylaxis to local anesthesia and hematoma.Evidence reviewWe systematically reviewed Pubmed, Central, EMBASE, Google Scholar, Web of Science citation index, the US clinical trials register, and abstracts for randomized controlled trials that compared these blocks and reported the rate of postoperative rescue analgesia.FindingsSeven RCTs (444 patients) were included in the final analysis. In pediatric abdominal surgery, compared with CB, QLB could reduce the rate of postoperative rescue analgesia within 24 h after surgery (RR = 0.37; 95% CI = 0.26 to 0.51; P < 0.01). The pain score in the QLB group at 4 (SMD = −0.11; 95% CI = −0.21 to −0.01; P = 0.02) and 12 h (SMD = −0.11; 95% CI = −0.22 to 0.00; P = 0.06) after surgery was lower, but at 0.5(SMD = 0.42; 95% CI = 0.34 to 0.50; P < 0.01) and 24 h (SMD = 0.30; 95% CI = 0.03 to 0.58; P = 0.03) was higher than that in the CB group. Of note, these pain score differences were not clinically significant. In addition, there was no significant difference in the incidence of complications or side effects between the QLB and the CB group (RR = 0.94; 95% CI = 0.59 to 1.48; P = 0.77).ConclusionIn conclusion, QLB might have a better postoperative analgesic effect for lower abdominal surgery than CB in pediatric patients. However, due to the relatively few RCTs identified and significant heterogeneity, further research in the future is needed to prove these findings.Systematic Review Registrationidentifier (CRD 42023441447).